2017
DOI: 10.1111/1556-4029.13561
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Due to Coronary Arteritis

Abstract: We report the case of a middle-aged man, without medical history, who suddenly died at his workplace. The autopsy highlighted a pathological heart macroscopically, with multiple small white areas on the left myocardium. Coronary dissection revealed a pseudotumoural fibromyxoid aspect within the anterior interventricular artery (AIVA) and the left main coronary trunk, including reduction in their diameter with tight stenosis. Microscopic examination of these arteries showed fibroinflammatory wall destruction. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Akiyama (1) reported that no tissue staining for IgG4 and IgG was conducted in our isolated coronary arteritis case report (2). IGg4‐related disease (IgG4RD) is a systemic disorder associating increase of serum IgG4 level, tissue infiltration of IgG4 positive plasma cells and fibrosis or sclerosis (3).…”
Section: Figmentioning
confidence: 99%
“…Akiyama (1) reported that no tissue staining for IgG4 and IgG was conducted in our isolated coronary arteritis case report (2). IGg4‐related disease (IgG4RD) is a systemic disorder associating increase of serum IgG4 level, tissue infiltration of IgG4 positive plasma cells and fibrosis or sclerosis (3).…”
Section: Figmentioning
confidence: 99%
“…Gabarrou et al (6) reported the case of a middle‐aged man with isolated coronary arteritis with unknown etiology. Their case presented with sudden cardiac death and the autopsy revealed the pseudotumoural macroscopic aspect of the anterior intraventricular artery with severe stenosis (>90%), indicating the diffuse wall thickening and stenotic type.…”
mentioning
confidence: 99%